Recent Advancements in Graphene Derivative-Based Nanocomposites: Innovations in Coating and Sensing Technologies - Khan, Nadia; Tabsi, Zahra A.; Zhang, Baiyu; Zhao, Yuming (Journal of Coating Science and Technology, 2024)
Graphene derivative-based nanocomposites have emerged as innovative solutions to address challenges in corrosion, marine biofouling, and environmental contamination. This review highlights recent advancements in three key areas: (1) dual-barrier and self-healing anti-corrosion materials, (2) eco-friendly anti-biofouling coatings, and (3) high-efficiency electrocatalytic films for electrochemical sensing. We emphasize the critical roles of graphene (Gr) sheets, graphene oxide (GO), and reduced graphene oxide (rGO) in enhancing nanocomposite performance through novel modifications with inorganic materials, organic polymers, and biomolecules. Key insights into advanced modification techniques and their impact on functionality and durability are presented. The review also explores graphene-enabled electrochemical sensors that showed high sensitivity to phenolic compounds in water. Mechanisms accounting for the improved performance of these materials are discussed, along with associated challenges such as scalability, cost-effectiveness, and stability. Future directions are suggested, focusing on sustainable, intelligent coatings and thin-film devices for environmental applications. This work aims to guide researchers, industry professionals, and policymakers in leveraging graphene-based technologies to tackle global issues in corrosion prevention, marine ecology, and environmental monitoring.